2011
DOI: 10.1021/nn201791k
|View full text |Cite
|
Sign up to set email alerts
|

Graphene as Cellular Interface: Electromechanical Coupling with Cells

Abstract: Interfacing cells with nanomaterials such as graphene, nanowires, and carbon nanotubes is useful for the integration of cellular physiology with electrical read outs. Here we show the interfacing of graphene sheets on the surface of yeast cells, leading to electromechanical coupling between the sheets and the cells. The cells are viable after the interfacing. The response caused by physiologically stressing the cells by exposure to alcohols, which causes a change in cell volume, can be observed in the electric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 35 publications
0
82
0
Order By: Relevance
“…[145] Therefore graphene provides a flexible and conducting substrate that interfaces well with the soft, 3D biological systems. [146][147][148] For example, the mechanical flexibility and electrical functions of graphene membrane can be used to achieve a strongly coupled electromechanical biointerface by coating yeast cells with an ultrathin layer of rGO (see also Fig. 7f).…”
Section: Graphene Lipid Superstructures: Towards Graphene Bioelectronicsmentioning
confidence: 99%
See 2 more Smart Citations
“…[145] Therefore graphene provides a flexible and conducting substrate that interfaces well with the soft, 3D biological systems. [146][147][148] For example, the mechanical flexibility and electrical functions of graphene membrane can be used to achieve a strongly coupled electromechanical biointerface by coating yeast cells with an ultrathin layer of rGO (see also Fig. 7f).…”
Section: Graphene Lipid Superstructures: Towards Graphene Bioelectronicsmentioning
confidence: 99%
“…7f). [147] Nevertheless, most researches on graphene biointerfaces still use graphene on rigid solid substrates at an intermediate stage mainly focusing on understanding the complicated sensing mechanisms (as the reconfiguration of the fluidic-like lipid layer has to be considered). [149,150,151] For example, a gram-negative bacteria biomimetic membrane was deposited on CVD GFETs (fabricated on a SiO 2 /Si substrate) for detecting magainin 2, an antimicrobial agent.…”
Section: Graphene Lipid Superstructures: Towards Graphene Bioelectronicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, graphene-based materials have excellent optical and electrochemical properties. It is used for constructing various types of cell-related bio-devices, which has good sensitivity [121]. These devices that are related to graphene have opened up a new dimension in the bio-medical field, with its eminent sensitive properties [107,122].…”
Section: Graphene In Cancer Cell Detectionmentioning
confidence: 99%
“…[25] Owing to these attributes, interfacing living cells with graphene can be useful for the integration of dynamic cellular physiology with electrical readouts. [26] Recently, several attempts have been made to interface graphene oxide (GO) with biomaterials: GO has been used for a membrane for DNA translocation, [27,28] quantitative measurement of the activity of helicase, [29] and a supportive material for cell culture. [30] Although these recent studies suggested the high potential of GO for biomaterials and biological systems, a tight interfacing of GO with whole living cells via encapsulation has not been attempted until now.…”
Section: Introductionmentioning
confidence: 99%